P147 Current smokers face increased risk of Acute Lung Injury post oesophagectomy compared to former smokers- implications for therapy and trial design?. (14th November 2013) - Dancer, RCA; Parekh, D; Calfee, CS; McAuley, DF; Perkins, GD; Thickett, DR
Abstract : Introduction: Patients undergoing oesophagectomy have 25% risk of developing post-operative Acute Lung Injury (ALI). A recent meta-analysis showed that smoking cessation prior to an operation reduces the risk of respiratory complications [1]. We hypothesised that current smokers would have an increased risk of ALI post-oesophagectomy compared with former smokers. Methods: We analysed data from 14 current smokers and 37 former smokers recruited to the translational sub-study of the BALTI prevention trial. Extravascular Lung Water Index (EVLWI) and Pulmonary Vascular Permeability Index (PVPI) were measured using PICCO. Plasma and Bronchoalveolar lavage fluid (BALF) cytokine levels were measured by ELISA. Results: Current smokers were significantly younger and had a lower BMI than former smokers. Current smokers were more likely to develop post-operative ALI which required ventilation but there was no difference in the rate of respiratory infection. PVPI was significantly higher immediately post op and on day 1 post op and EVLWI was significantly higher on day 1 post op in current smokers (see table). Plasma levels of FAS ligand were significantly lower in current smokers pre-op, post-op and on day 1 post-op. Pre-op plasma levels of sICAM1 were significantly higher in current smokers but there was no difference in post-op levels. Plasma levels of IL-17 were lower pre-op, post-op and on day 1, although only the post-op difference reached significance. In BAL, levels of VEGF were significantly lower and levels of IL1ra and TNFR1 were significantly higher in current smokers (see table). Conclusion: Current smokers have a higher risk of Acute Lung Injury following oesophagectomy than former smokers. This finding is supported by higher post-operative levels of extravascular lung water and pulmonary vascular permeability and differences in both plasma and BAL cytokines in current smokers. Our data highlights the importance of encouraging patients to stop smoking prior to major surgery as well as the need to control for smoking history in trials aiming to ameliorate lung injury in this patient group. References: Wong, J. et al . Short-term preoperative smoking cessation and postoperative complications: a systematic review and meta-analysis. Can J Anaesth, 2012. 59(3): 268–79